Digital HRM Transformation by Artificial Intelligent (AI) - Zulkifli Djamin; Dasmadi (Jurnal Penelitian Pendidikan IPA, 2024)
Humans are gradually being substituted by of artificial intelligence and robots in virtually all departments in organizations. For some workers this might mean they have to find a new job, or a new orientation in terms of skills. Whatsoever, this revolution is upsetting the workforce. Human Resource professionals now have the responsibility of overseeing the placement of robots and AI, ensuring that everything goes smoothly, and intervening when problems arise. This thesis pertains examining the utilization in the workplace of AI, robot alongside man- power from the HRM standpoint. In the first section, there is a discussion on the introduction, objectives, the set-up of the problem, the delimitations and lastly, the concept of using manpower, AI, and robot at the workplace. In the second section, there is the demonstration of theoretical and the empirical parts of the thesis. This research is a literature review of several articles related to machine learning. The review was conducted from some of the recent research efforts that utilize machine learning. Furthermore, this review is derived from multiple literacies and includes an attempt at problem solving efforts that are divided into section areas from the perspective of each machine learning category. Machine learning can change the way the human resource management domain functions in an organization. It is making changes in all aspects of human resource management starting from human resource planning. Enormous data is available in human resource information systems (HRIS) available in organizations.